(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper is concerned with the concepts of upper rarely s-(τ_1,τ_2)p-continuous multifunctions and lower rarely s-(τ_1,τ_2)p-continuous multifunctions. Furthermore, some characterizations and several properties concerning upper rarely s-(τ_1,τ_2)p-continuous multifunctions and lower rarely s-(τ_1,τ_2)p-continuous multifunctions are established.